EKSISTENSI RUMAH MENTERI KERAJAAN INDRAGIRI SEBAGAI CAGAR BUDAYA - Dwi Yulia Srikandi (Jurnal Budaya Nusantara, 2021)
Existence is defined as existence. Where the existence is meant is the influence of our presence orabsence. This existence needs to be “given” by other people to us, because the response from people around us proves that our existence is acknowledged. The issue of the need for the value of existence is very important, because it is a proof of work or performance in an environment. Thisstudy discusses (1) the process of the Indragiri Kingdom Minister’s House as a CulturalConservation; (2) Efforts made by the Government in Managing the House of the Minister of the Kingdom of Indragiri as a Cultural Conservation; (3) The existence of the House of the Minister of the Kingdom of Indragiri as a Cultural Conservation. This type of research is qualitative research with a descriptive method, namely describing the answers through observation, interviews from informants and documentation and literature study. The collection of sources was obtained from the Regional Library of Indragiri Hulu Regency, Prof.Suwardi Library, Soeman H.S Pekanbaru Regional Library. As well as conducting interviews with families as heirs, historical observers of Indragiri Hulu Regency, related agencies and the people of Indragiri Hulu Regency, especially in the vicinity of the Cultural Heritage building. The results of the study showthat the House of the Minister of Maritime Affairs of the Indragiri Kingdom still visits not only local people but also national and even international tourists such as Malaysia, although experiencing ups and downs.